Use of sludge tannery substrate as alternative to prepare conilon coffee seedlings - Berilli, Sávio Silva; Quiuqui, Joao Paulo Chodacki; Rembinski, Jessica; Salla, Paulo Henrique Honorato; Berilli, Ana Paula Candido Gabriel; Louzada, João Marcos (Coffee Science - ISSN 1984-3909, 2014)
The Brazilian cattle is great source of income and investments from public and private sectors, and after slaughter, the destination of the leather to tannery causes the generation of a significant amount of waste in the form of sludge, thus becoming an environmental problem for tanneries in many Brazilian states that do not have laws for proper disposal of this waste. Thus, the use of sludge in agriculture tanneries presented as a solution technically feasible due to the high amounts of nutrients available in the sludge, such as calcium, sulfur, magnesium, nitrogen and organic matter. This paper, therefore, aims to evaluate the influence of different concentrations of dehydrated tannery sludge to produce Conilon coffee seedlings compared to conventional fertilization. The experiment was arranged as a randomized block design consisting of five treatments, four ratios of dewatered sludge (10, 20, 30 and 40% silt) and the other one with a substrate for the production of conventional Conilon coffee seedlings. For this experiment, we evaluated the biometric characteristics of the seedlings, we observed that the conventional fertilization showed better seedling development evaluated, however, we also observed that treatments with concentrations 20 and particularly 30 % of dehydrated tannery sludge in the substrate showed no significant differences for most characteristics evaluated in relation to treatment with conventional fertilization , thus demonstrating its potential use in substrate seedlings.